A Comparative Study of Pedagogical Skills of Educators in Rural and Urban Secondary Schools - Dr. Muhammad Shahzad Ashfaq (Journal for Social Science Archives, 2025)
This study aims to investigate the pedagogical skills of educators in secondary schools located in both rural and urban areas. The main objective is to examine the differences in pedagogical skills between educators from rural and urban schools and to identify the underlying causes of these differences. The population of the study comprised secondary school educators in Tehsil Kaller Syedan. Using a convenient sampling technique, a sample of 40 educators was selected from 10 secondary schools—five from rural areas and five from urban areas. Data were collected through a structured survey questionnaire, and the analysis was conducted using SPSS version 21. The findings revealed significant differences in the pedagogical skills of educators, particularly in teaching methodologies, the use of audiovisual (A.V.) aids, and the application of reinforcement techniques. It was observed that A.V. aids were often unavailable and laboratories were not adequately maintained in many schools, especially in rural areas. These disparities were primarily attributed to a lack of resources in rural schools. The study concludes that resource limitations in rural areas significantly affect the pedagogical practices of educators.